Railroad Crossings Seen from Indonesia's Positive Law - Churniawan, Erifendi; Masdini Agustriana, Titiek; Priyanto, Sapto (Riviera Publishing, 2022)
Introduction: Rail transportation is part of land transportation in Indonesia. The extended rail network has level crossings, namely the crossing of railroads and highways. Judging from the existing laws in Indonesia, the law mentions avoiding accidents at level crossings. Several factors influence law enforcement at railroad crossings, including legal, law enforcement, facilities, community, and cultural factors. There needs to be legal awareness from the side of law violators themselves, law enforcement officers themselves, and the government side. It is also necessary to increase cooperation between networks of law enforcement officers in crossing railroad crossings. Method: The research method used in this study is comparative descriptive. Result: The public is stated to have not understood the regulations that discuss railroad crossings listed in Law Number 23 of 2007, which discusses railways. In Law Number 22 of 2009, which discusses Traffic and Road Transportation, it is stated that Government Regulation 56 of 2009 discusses the Implementation of Railways and Government Regulation Number 72 of 2009 concerning Railway Traffic and Transportation. Conclusion: The law of crossing a railroad plot according to positive law in Indonesia has a position as a reference for travelling a railroad plot as has been written based on: Article 124 of Law Number 23 of 2007, Article 78 of Government Regulation Number 56 of 2009, Article 110 paragraph (1) Government Regulation Number 72 of 2009 & Article 114 of Law Number 22 of 2009.